Nitrogen-doped hard carbon material, preparation method and application thereof, pole piece and electrochemical device
By heat-treating the mixture of porous carbon and g-C3N4, nitrogen-doped hard carbon materials were prepared, which solved the problem of low capacity and first-effect of existing materials, and achieved capacity improvement and first-effect improvement of lithium-ion batteries.
Patent Information
- Application Number
- CN202411998544.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Existing nitrogen-doped hard carbon materials have lower capacity and first-term effects in lithium-ion batteries.
By heat-treated the mixture of porous carbon and g-C3N4, a nitrogen-doped hard carbon material was prepared, and a graphite-like microcrystalline structure was formed by combining the doped form of edge nitrogen and the addition of g-C3N4.
The specific surface area and lithium storage capacity of nitrogen-doped hard carbon materials have been improved, and the capacity and first-term effect of lithium-ion batteries have been improved.
Smart Images

Figure CN119797321A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a nitrogen-doped hard carbon material and a preparation method, application, pole piece and electrochemical device thereof. Background Art
[0002] With the advancement of science and technology and the rapid development of society, the requirements for lithium-ion batteries are getting higher and higher. With the accelerated pace of life, people are beginning to want to improve the performance of lithium-ion batteries. The negative electrode materials used in current products are generally graphite materials, but their specific capacity has reached the upper limit, the structure lacks long-term stability, and it is difficult to maintain long-term high-current discharge. Therefore, it is necessary to develop alternative materials with excellent performance. Compared with graphite, hard carbon has isotropic structural characteristics, amorphous microstructure, and large interlayer spacing, which is conducive to the rapid diffusion of lithium ions. It has excellent cycle performance, rate performance and safety, which has once again attracted attention in power lithium-ion batteries.
[0003] However, hard carbon also has the disadvantages of low first-cycle coulombic efficiency and low reversible capacity, and needs to be doped and modified to obtain higher coulombic efficiency. At the same time, the active sites of carbon materials can be increased by doping modification, thereby improving the lithium storage capacity of the material. CN109301220A discloses a method for preparing nitrogen-doped hard carbon materials, which acid-washes plant resources and then immerses them in a nitrogen source aqueous solution to obtain a pre-product; then, under a protective atmosphere, the pre-product is heat-treated to obtain a nitrogen-doped hard carbon material with a porous structure. CN109768218A discloses a nitrogen-doped hard carbon lithium-ion battery negative electrode material. The patent hydrothermally treats the biomass carbon source, and then evenly mixes it with a choline chloride-type ionic liquid in proportion, first pre-treats it, and then carbonizes it at high temperature to obtain a biomass carbon material doped with nitrogen, which can be used as a negative electrode material for lithium-ion batteries. By doping nitrogen in hard carbon materials, the capacity can be increased to a certain extent, but excessive doping increases surface defects, which will lead to a decrease in the first efficiency. Summary of the invention
[0004] The purpose of the present invention is to solve the problem of low capacity and initial efficiency of existing nitrogen-doped hard carbon materials, and to provide a nitrogen-doped hard carbon material and its preparation method, application, pole piece and electrochemical device. The nitrogen-doped hard carbon material of the present invention has good capacity and high initial efficiency.
[0005] The present invention solves the above technical problems through the following technical solutions:
[0006] The present invention provides a method for preparing a nitrogen-doped hard carbon material, which comprises the following steps: subjecting a mixture A to a first heat treatment to obtain a nitrogen-doped hard carbon material;
[0007] The mixture A includes porous carbon and g-C3N4.
[0008] In some embodiments of the present invention, the mass ratio of the porous carbon to the g-C3N4 is 1:(0.5-2), preferably 1:(0.8-1.2), for example 1:0.5, 1:1 or 1:2.
[0009] In some embodiments of the present invention, the temperature of the first heat treatment is 1000-1200°C, for example, 1000°C or 1200°C.
[0010] In some embodiments of the present invention, the time of the first heat treatment is 1 to 4 hours, for example, 2 hours.
[0011] In some embodiments of the present invention, the method for preparing the mixture A includes: mixing the porous carbon and the g-C3N4 to obtain the mixture A.
[0012] In some embodiments of the present invention, the specific surface area of the porous carbon is 150 to 800 m 2 / g, preferably 300-400m 2 / g, for example 235.4m 2 / g, 373.6m 2 / g or 693.6m 2 / g.
[0013] In some embodiments of the present invention, the average pore size of the porous carbon is 1 to 15 nm, preferably 1 to 6 nm, more preferably 2 to 5 nm, such as 1.5 nm, 2.7 nm or 10.2 nm.
[0014] In some embodiments of the present invention, the total pore volume of the porous carbon is 0.1 to 1.0 cm 3 / g, preferably 0.2-0.5cm 3 / g, for example 0.12cm 3 / g, 0.46cm 3 / g or 0.6cm 3 / g.
[0015] In some embodiments of the present invention, the volume of micropores in the porous carbon accounts for 20-95% of the total pore volume of the porous carbon, preferably 50-80%, such as 21%, 70% or 90%.
[0016] In the present invention, the particle size of the porous carbon is the conventional market-demanded particle size in the art. In some embodiments, the D50 particle size of the porous carbon is 5 to 10 μm, for example, 5 μm.
[0017] In the present invention, the porous carbon can be commercially available or prepared by conventional methods in the art.
[0018] In some embodiments of the present invention, the method for preparing porous carbon comprises the following steps:
[0019] (1) subjecting the asphalt to a second heat treatment in an oxygen-containing atmosphere to obtain a preliminary material, wherein the temperature of the second heat treatment is higher than the softening point of the asphalt;
[0020] (2) performing a third heat treatment on the mixture B to obtain porous carbon; the mixture B includes the preliminary material and a zinc source; and the temperature of the third heat treatment is higher than the evaporation temperature of the zinc source.
[0021] In the present invention, the temperature of the second heat treatment is related to the softening point of the asphalt.
[0022] In some embodiments of the present invention, the temperature of the second heat treatment is 20-30° C. higher than the softening point of the asphalt.
[0023] In some embodiments of the present invention, the softening point of the asphalt is 180-300° C., for example, 200° C. If the softening point of the asphalt is too low, more light components will be produced, resulting in lower yields. If the softening point is too high, the cost will be higher. Preferably, the softening point is 180-300° C.
[0024] In some embodiments of the present invention, the temperature of the second heat treatment is 150-300°C.
[0025] In some embodiments of the present invention, the second heat treatment time is 12 to 24 hours, for example, 16 hours.
[0026] In the present invention, if the D50 particle size of the asphalt is too large, the internal oxidation will not be in place, and if the particle size is too small, the powder is not easy to process. In some of the solutions, the D50 particle size of the asphalt is 5 to 20 μm, for example, 10 μm.
[0027] In the present invention, the oxygen-containing atmosphere is conventional in the art, and in some embodiments, the oxygen-containing atmosphere is an air atmosphere.
[0028] In some embodiments of the present invention, the gas flow rate of the oxygen-containing atmosphere is 1 to 5 L / min, for example, 2 L / min.
[0029] In some embodiments of the present invention, the step of crushing the asphalt is further included before subjecting the asphalt to the second heat treatment.
[0030] The pulverization is conventional in the art, such as air jet mill or rod mill. The air jet mill preferably adopts a flat air jet mill device, the classification frequency of the flat air jet mill device is preferably 25-40 Hz, such as 30 Hz, and the fan frequency is preferably 20-30 Hz, such as 25 Hz;
[0031] In the present invention, the zinc source is a conventional zinc source for pore formation in the art. In some embodiments, the zinc source is a zinc compound, and the zinc compound is preferably any one or more of ZnCl2, zinc acetate and zinc acetate.
[0032] In some embodiments of the present invention, the mass ratio of the preliminary material to the zinc source is 1:(0.2-2.5), preferably 1:(0.4-0.6), for example 1:0.5, 1:1 or 1:2.
[0033] In the present invention, the temperature of the third heat treatment is related to the evaporation temperature of the zinc source.
[0034] In some embodiments of the present invention, the temperature of the third heat treatment is 850-950°C, for example, 900°C.
[0035] In some embodiments of the present invention, the duration of the third heat treatment is 2 to 6 hours, for example, 4 hours.
[0036] In some embodiments of the present invention, the third heat treatment is performed in an inert protective gas, which is conventional in the art, such as nitrogen and / or argon.
[0037] In some embodiments of the present invention, after the mixture B is subjected to the third heat treatment, the step of crushing and screening the porous carbon is further included.
[0038] The pulverization is conventional in the art, such as air jet mill or rod mill. The air jet mill preferably adopts a flat air jet mill device, the classification frequency of the flat air jet mill device is preferably 50-70 Hz, such as 60 Hz, and the fan frequency is preferably 30-50 Hz, such as 40 Hz.
[0039] The screening is performed using a conventional sieve in the art, and the particle size of the porous carbon after screening is 5 to 10 μm.
[0040] In the present invention, the particle size of the g-C3N4 is conventional in the art. In some embodiments, the D50 particle size of the g-C3N4 is 5 to 20 μm, for example, 5 μm.
[0041] The present invention also provides a nitrogen-doped hard carbon material prepared by the above-mentioned method for preparing the nitrogen-doped hard carbon material.
[0042] The present invention also provides a nitrogen-doped hard carbon material, which includes porous hard carbon particles and nitrogen doped in the porous hard carbon particles, wherein the nitrogen includes edge nitrogen;
[0043] The specific surface area of the nitrogen-doped hard carbon material is 5 to 100 m 2 / g;
[0044] The nitrogen-doped hard carbon material includes a graphite-like microcrystalline structure.
[0045] In some embodiments of the present invention, the nitrogen content is 2-7%, for example 2%, 3.2%, 5%, 5.6% or 7%, which refers to the mass fraction of nitrogen in the nitrogen-doped hard carbon material.
[0046] In some embodiments of the present invention, the edge nitrogen is pyrrolic nitrogen and / or pyridinic nitrogen.
[0047] In some embodiments of the present invention, the specific surface area of the nitrogen-doped hard carbon material is 10 to 60 m 2 / g, for example 10.7m 2 / g, 12.1m 2 / g, 18.4m 2 / g, 21.3m 2 / g, 32.6m 2 / g or 54.5m 2 / g.
[0048] In some embodiments of the present invention, the total pore volume of the nitrogen-doped hard carbon material is 0.005 to 0.1 m 2 / g, preferably 0.008-0.05m 2 / g, for example 0.009m 2 / g, 0.012m 2 / g, 0.013m 2 / g, 0.022m 2 / g, 0.023m 2 / g or 0.034m 2 / g.
[0049] In some embodiments of the present invention, the average pore size of the nitrogen-doped hard carbon material is 1-3 nm, preferably 1.5-2 nm, such as 1.5 nm, 1.7 nm, 1.8 nm, 2.1 nm or 2.5 nm.
[0050] In some embodiments of the present invention, the volume of the micropores of the nitrogen-doped hard carbon material accounts for 35-70% of the total pore volume of the nitrogen-doped hard carbon material, preferably 50-60%, for example 42.7%, 44.7%, 50.1%, 52.1%, 52.3% or 54.3%.
[0051] In the present invention, "micropores" refer to pores with a pore diameter of less than 2 nm.
[0052] In some embodiments of the present invention, the D50 particle size of the porous hard carbon particles is 5-10 μm, for example, 5 μm.
[0053] The present invention also provides an application of the above-mentioned nitrogen-doped hard carbon material as a negative electrode material in a lithium-ion battery.
[0054] The present invention also provides a pole piece, which comprises the aforementioned nitrogen-doped hard carbon material.
[0055] The present invention also provides an electrochemical device, which comprises the above-mentioned pole piece.
[0056] The positive and progressive effects of the present invention are:
[0057] The present invention heat-treats a mixture of porous carbon and g-C3N4 to obtain a nitrogen-doped hard carbon material with a low specific surface area. Using the nitrogen-doped hard carbon material in a lithium-ion battery material can improve the first efficiency of the battery. At the same time, the nitrogen in the nitrogen-doped hard carbon material of the present invention is doped in the carbon in the form of edge nitrogen, and the addition of g-C3N4 can promote the increase of the graphite-like microcrystalline structure of the carbon material. Using the nitrogen-doped hard carbon material in a lithium-ion battery material can improve the capacity while ensuring a good first efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 Graphs showing nitrogen adsorption-desorption isotherms of the nitrogen-doped hard carbon materials of Examples 1 to 3.
[0059] Figure 2 This is the first charge and discharge curve of the nitrogen-doped hard carbon material of Example 2.
[0060] Figure 3 1 and 2 are XRD graphs of the nitrogen-doped hard carbon material of Example 2 and the hard carbon material of Comparative Example 1. DETAILED DESCRIPTION
[0061] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0062] In the following examples, g-C3N4 was purchased from MacLean Reagent Network, and zinc chloride powder was industrial grade zinc chloride.
[0063] The nitrogen content in the following examples is tested using an EDS surface scanning method.
[0064] Example 1
[0065] (1) LQ-200 (softening point 200°C) asphalt was ground to a particle size D50 = 10 μm using a flat jet mill with a grading frequency of 30 Hz and a fan frequency of 25 Hz;
[0066] (2) Add the crushed asphalt material into the drum furnace, with the material volume accounting for half of the drum furnace volume, under air atmosphere, with a gas flow rate of 2 L / min, and a constant temperature of 220-230° C. for 16 hours, and obtain the preliminary material after cooling;
[0067] (3) The preliminary material and zinc chloride powder were mixed uniformly in a mass ratio of 1:0.5 and loaded into a graphite crucible, and pre-carbonized in an atmosphere furnace under a nitrogen atmosphere at a carbonization temperature of 900°C. The mixture was kept at 900°C for 4 hours to obtain porous carbon, which was named DK-BHC-0.5.
[0068] (4) The DK-BHC-0.5 obtained in step (3) is crushed to a particle size of D50 = 5 μm using a flat air flow mill, the grading frequency of the flat air flow mill is 60 Hz, and the fan frequency is 40 Hz; then the crushed material is mixed with g-C3N4 with a D50 particle size of 5 μm in a mass ratio of 1:1, the mixed material is loaded into a graphite crucible, and then kept in a nitrogen atmosphere at 1000°C for 2 h, and then naturally cooled to obtain a nitrogen-doped hard carbon material.
[0069] The nitrogen content of the nitrogen-doped hard carbon material is 4.3%.
[0070] Example 2
[0071] (1) LQ-200 (softening point 200°C) asphalt was ground to a particle size D50 = 10 μm using a flat jet mill with a grading frequency of 30 Hz and a fan frequency of 25 Hz;
[0072] (2) Add the crushed asphalt material into the drum furnace, the material volume accounts for half of the drum furnace volume, under air atmosphere, the gas flow rate is 2L / min, the temperature is kept at 220-230°C for 16 hours, and the preliminary material is obtained after cooling;
[0073] (3) The preliminary material and zinc chloride powder were mixed in a mass ratio of 1:1 and uniformly loaded into a graphite crucible, and pre-carbonized in an atmosphere furnace under a nitrogen atmosphere at a carbonization temperature of 900°C. The mixture was kept at 900°C for 4 hours to obtain porous carbon, which was named DK-BHC-1.
[0074] (4) The DK-BHC-1 obtained in step (3) is crushed to a particle size of D50 = 5 μm using a flat air flow mill, the grading frequency of the flat air flow mill is 60 Hz, and the fan frequency is 40 Hz; then the crushed material is mixed with g-C3N4 with a D50 particle size of 5 μm in a mass ratio of 1:1, the mixed material is loaded into a graphite crucible, and then kept in a nitrogen atmosphere at 1000°C for 2 h, and then naturally cooled to obtain a nitrogen-doped hard carbon material.
[0075] The nitrogen content of the nitrogen-doped hard carbon material is 5%.
[0076] Example 3
[0077] (1) LQ-200 (softening point 200°C) asphalt was ground to a particle size D50 = 10 μm using a flat jet mill with a grading frequency of 30 Hz and a fan frequency of 25 Hz;
[0078] (2) Add the crushed asphalt material into the drum furnace, with the material volume accounting for half of the drum furnace volume, under air atmosphere, with a gas flow rate of 2 L / min, and a constant temperature of 220-230° C. for 16 hours, and obtain the preliminary material after cooling;
[0079] (3) The preliminary material and zinc chloride powder were mixed in a mass ratio of 1:2 and uniformly loaded into a graphite crucible, and pre-carbonized in an atmosphere furnace under a nitrogen atmosphere at a carbonization temperature of 900°C. The mixture was kept at 900°C for 4 hours to obtain porous carbon, which was named DK-BHC-2.
[0080] (4) The DK-BHC-2 obtained in step (3) is crushed to a particle size of D50 = 5 μm using a flat air flow mill, the grading frequency of the flat air flow mill is 60 Hz, and the fan frequency is 40 Hz; then the crushed material is mixed with g-C3N4 with a D50 particle size of 5 μm in a mass ratio of 1:1, the mixed material is loaded into a graphite crucible, and then kept in a nitrogen atmosphere at 1000°C for 2 h, and then naturally cooled to obtain a nitrogen-doped hard carbon material.
[0081] The nitrogen content of the nitrogen-doped hard carbon material is 5.6%.
[0082] Example 4
[0083] This embodiment is basically the same as Embodiment 2, except that in step (4), the mass ratio of the crushed material to g-C3N4 is 1:0.5.
[0084] The nitrogen content of the nitrogen-doped hard carbon material is 2%.
[0085] Example 5
[0086] This embodiment is basically the same as Embodiment 2, except that in step (4), the mass ratio of the crushed material to g-C3N4 is 1:2.
[0087] The nitrogen content of the nitrogen-doped hard carbon material is 7%.
[0088] Example 6
[0089] This embodiment is basically the same as embodiment 2, except that in step (4), the carbonization temperature is 1200°C.
[0090] The nitrogen content of the nitrogen-doped hard carbon material is 3.2%.
[0091] Comparative Example 1
[0092] This comparative example is basically the same as Example 2, except that: in step (4), no g-C3N4 is added, and the crushed material is directly carbonized at 1000°C for 2 h in a nitrogen atmosphere to obtain a hard carbon material.
[0093] Effect Example
[0094] 1. Porous carbon pore structure parameters
[0095] The specific surface area, average pore diameter, total pore volume and micropore ratio of the porous carbon prepared in Examples 1 to 3 were tested, and the results are shown in Table 1.
[0096] The pore structure parameters of porous carbon were tested by nitrogen adsorption and desorption method, specifically, ASAP 2460 instrument was used for testing. First, a certain amount of porous carbon sample was weighed into a sample tube, the sample was vacuum degassed at 300 °C for 4 hours, and then analyzed and tested in a liquid nitrogen environment. After the test was completed, the HS-2D-NLDFT, Carbon, N2, 77 analysis model was used to analyze the pore structure of the test results to obtain the specific surface area, average pore size, total pore volume and micropore ratio.
[0097] Figure 1 Shown are the porous carbon nitrogen adsorption-desorption isotherms of Examples 1 to 3.
[0098] Table 1
[0099] Sample name <![CDATA[Specific surface area (m 2 / g)]]> Average pore size (nm) <![CDATA[Total pore volume (cm 3 / g)]]> Micropore ratio (%) DK-BHC-0.5 235.4 1.5 0.12 90 DK-BHC-1 373.6 2.7 0.46 70 DK-BHC-2 693.6 10.2 0.6 21
[0100] 2. Pore structure parameters of nitrogen-doped hard carbon materials
[0101] The specific surface area, average pore diameter, total pore volume and micropore ratio of the nitrogen-doped hard carbon material of the above embodiment and the hard carbon material of the comparative example were tested, and the results are shown in Table 2. The test method is the same as the test method of porous carbon.
[0102] Table 2
[0103] Sample name <![CDATA[Specific surface area (m 2 / g)]]> Average pore size (nm) <![CDATA[Total pore volume (cm 3 / g)]]> Micropore ratio (%) Example 1 32.6 2.1 0.022 44.7 Example 2 12.1 1.7 0.013 54.3 Example 3 54.5 2.5 0.034 42.7 Example 4 21.3 1.8 0.023 52.1 Example 5 18.4 1.7 0.012 50.1 Example 6 10.7 1.5 0.009 52.3 Comparative Example 1 132.1 3.1 0.12 32.1
[0104] 3. Electrochemical performance test
[0105] The electrodes were prepared using the nitrogen-doped hard carbon material of the above embodiment and the hard carbon material obtained in the comparative example and assembled into a battery. The preparation method of the battery is as follows:
[0106] The nitrogen-doped hard carbon material of the above embodiment or the hard carbon material of the comparative example, the binder (CMC), and the superconducting carbon black (SP) were placed in a vacuum oven at a mass ratio of 8:1:1, vacuum dried at 80°C for 24h, stirred with water as a solvent for 1h, and dispersed until there were no obvious particles to obtain a negative electrode slurry. Each of the obtained negative electrode slurries was evenly coated on a copper foil, and then dried at 80°C for 12h, and punched into a negative electrode sheet with a diameter of 12mm. The prepared negative electrode sheet was placed in the center of the negative electrode shell, and then the diaphragm (the diaphragm is a composite film of polyethylene PE, polypropylene PP and polyethylene propylene PEP) was gently placed on it, and an appropriate amount of electrolyte LPF6 (EC:DMC:EMC-1:1:1V%) was dripped, and then the metal lithium sheet gasket and the shrapnel were placed, and finally the positive electrode shell was covered. After the assembly was completed, a hydraulic sealing machine was used to seal and wipe the excess electrolyte on its surface. The assembly process was completed in a glove box, wherein the water content and oxygen content in the glove box were controlled below 0.5ppm. Put the assembled battery into a battery box and place it in a constant temperature box for 12 hours to obtain a CR2032 button battery.
[0107] The charge and discharge test parameters are as follows: The test instrument used is Shenzhen Xinweier Battery Tester. Test conditions: constant temperature (25℃), first discharge to 0V at 0.2C, let stand for 10 minutes, then discharge to 0V at 0.02C, and finally charge to 2V at 0.2C.
[0108] The test results are shown in Table 3.
[0109] Table 3 Electrochemical performance test results
[0110] Sample name First discharge capacity (mAh / g) First charge capacity (mAh / g) First charge and discharge efficiency (%) Example 1 684 438 64 Example 2 713 563 79 Example 3 849 501 59 Example 4 621 454 73 Example 5 756 537 71 Example 6 601 463 77 Comparative Example 1 468 253 54
[0111] Test result analysis:
[0112] It can be seen from Example 2 and Comparative Example 1 that doping g-C3N4 can effectively reduce its specific surface area, and nitrogen atom doping provides more lithium storage sites and improves capacity. Figure 3 It can be seen that the interlayer spacing of the porous hard carbon doped with g-C3N4 is smaller than that of the porous hard carbon undoped with g-C3N4, D002 of Implementation Case 2 is 0.36nm, and D002 of Comparative Example 1 is 0.37nm. The 002 peak of Implementation Case 2 is obviously shifted to the right, and the peak intensity of the 002 peak of Implementation Case 2 is increased, and the peak width is narrowed, indicating that its graphite crystallites are more than that of Comparative Example 1.
[0113] It can be seen from Example 2, Example 1 and Example 3 that porous carbon with more micropores and suitable pore volume provides more active sites for lithium storage after doping with g-C3N4. In the first charge and discharge test, the first discharge capacity is 713mAh / g, the first charge capacity is 563mAh / g, and the first efficiency is 79%;
[0114] It can be seen from Example 2, Example 4 and Example 5 that a suitable doping amount of g-C3N4 is more beneficial to the improvement of capacity. Too little g-C3N4 (such as Example 4) cannot provide enough lithium storage sites, and too much g-C3N4 (such as Example 5) can provide more lithium storage active sites, but will reduce the initial effect.
[0115] It can be seen from Example 2 and Example 6 that too high carbonization temperature of porous carbon and g-C3N4 will affect the capacity and reduce the first efficiency.
Claims
1. A method for preparing a nitrogen-doped hard carbon material, characterized in that: It includes the following steps: The mixture A is subjected to a first heat treatment to obtain a nitrogen-doped hard carbon material; The mixture A includes porous carbon and g-C3N4.
2. The method for preparing a nitrogen-doped hard carbon material according to claim 1, wherein: The method for preparing the nitrogen-doped hard carbon material satisfies one or more of the following conditions: (a) The mass ratio of the porous carbon to the g-C3N4 is 1:(0.5-2), preferably 1:(0.8-1.2), for example 1:0.5, 1:1 or 1:2; (b) the temperature of the first heat treatment is 1000-1200° C., for example 1000° C. or 1200° C.; (c) the first heat treatment time is 1 to 4 hours, for example 2 hours; (d) The preparation method of the mixture A comprises: mixing the porous carbon and the g-C3N4 to obtain the mixture A.
3. The method for preparing a nitrogen-doped hard carbon material according to claim 1, characterized in that: The porous carbon satisfies one or more of the following conditions: (a) The specific surface area of the porous carbon is 150 to 800 m 2 / g, preferably 300-400m 2 / g, for example 235.4m 2 / g, 373.6m 2 / g or 693.6m 2 / g; (b) the average pore size of the porous carbon is 1 to 15 nm, preferably 1 to 6 nm, more preferably 2 to 5 nm, for example 1.5 nm, 2.7 nm or 10.2 nm; (c) The total pore volume of the porous carbon is 0.1 to 1.0 cm 3 / g, preferably 0.2-0.5cm 3 / g, for example 0.12cm 3 / g, 0.46cm 3 / g or 0.6cm 3 / g; (d) the volume of the micropores in the porous carbon accounts for 20-95% of the total pore volume of the porous carbon, preferably 50-80%, for example 21%, 70% or 90%; (e) the D50 particle size of the porous carbon is 5 to 10 μm, for example 5 μm; (f) The D50 particle size of the g-C3N4 is 5 to 20 μm, for example, 5 μm.
4. The method for preparing a nitrogen-doped hard carbon material according to claim 1, characterized in that: The method for preparing the porous carbon comprises the following steps: (1) subjecting the asphalt to a second heat treatment in an oxygen-containing atmosphere to obtain a preliminary material, wherein the temperature of the second heat treatment is higher than the softening point of the asphalt; (2) performing a third heat treatment on the mixture B to obtain porous carbon; the mixture B includes the preliminary material and a zinc source; the temperature of the third heat treatment is higher than the evaporation temperature of the zinc source; Preferably, the method for preparing the porous carbon satisfies one or more of the following conditions: (a) the temperature of the second heat treatment is 20 to 30° C. higher than the softening point of the asphalt; (b) the softening point temperature of the asphalt is 180-300°C, for example 200°C; (c) the temperature of the second heat treatment is 150 to 300° C.; (d) the second heat treatment time is 12 to 24 hours, for example 16 hours; (e) the D50 particle size of the asphalt is 5 to 20 μm, for example, 10 μm; (f) the oxygen-containing atmosphere is an air atmosphere; (g) the gas flow rate of the oxygen-containing atmosphere is 1 to 5 L / min, for example 2 L / min; (h) before subjecting the asphalt to the second heat treatment, the asphalt is further subjected to a pulverizing step, wherein the pulverizing step is preferably performed by a jet mill or a rod mill, wherein the jet mill is preferably a flat jet mill device, wherein the grading frequency of the flat jet mill device is preferably 25 to 40 Hz, for example, 30 Hz, and the fan frequency is preferably 20 to 30 Hz, for example, 25 Hz; (i) the zinc source is a zinc compound, and the zinc compound is preferably any one or more of ZnCl2, zinc acetate and zinc acetate; (j) the mass ratio of the preliminary material to the zinc source is 1:(0.2-2.5), preferably 1:(0.4-0.6), for example 1:0.5, 1:1 or 1:2; (k) the temperature of the third heat treatment is 850-950° C., for example, 900° C.; (l) the third heat treatment lasts for 2 to 6 hours, for example 4 hours; (m) the third heat treatment is performed in an inert protective gas, and the inert protective gas is preferably nitrogen and / or argon; (n) After the mixture B is subjected to the third heat treatment, the step of crushing and screening the porous carbon is also included; the crushing is preferably performed by air flow milling or rod grinding, the air flow mill is preferably a flat air flow mill device, the grading frequency of the flat air flow mill device is preferably 50 to 70 Hz, for example, 60 Hz, and the fan frequency is preferably 30 to 50 Hz, for example, 40 Hz; the screening The particle size of the porous carbon is 5 to 10 μm.
5. A nitrogen-doped hard carbon material prepared by the method for preparing a nitrogen-doped hard carbon material according to any one of claims 1 to 4.
6. A nitrogen-doped hard carbon material, characterized in that: It includes porous hard carbon particles and nitrogen doped in the porous hard carbon particles, wherein the nitrogen includes edge nitrogen; The specific surface area of the nitrogen-doped hard carbon material is 5 to 100 m 2 / g; The nitrogen-doped hard carbon material includes a graphite-like microcrystalline structure.
7. The nitrogen-doped hard carbon material according to claim 6, wherein The nitrogen-doped hard carbon material satisfies one or more of the following conditions: (a) the nitrogen content is 2-7%, for example 2%, 3.2%, 5%, 5.6% or 7%, % refers to the mass fraction of nitrogen in the nitrogen-doped hard carbon material; (b) the edge nitrogen is pyrrolic nitrogen and / or pyridinic nitrogen; (c) The specific surface area of the nitrogen-doped hard carbon material is 10 to 60 m 2 / g, for example 10.7m 2 / g, 12.1m 2 / g, 18.4m 2 / g, 21.3m 2 / g, 32.6m 2 / g or 54.5m 2 / g; (d) The total pore volume of the nitrogen-doped hard carbon material is 0.005 to 0.1 m 2 / g, preferably 0.008-0.05m 2 / g, for example 0.009m 2 / g, 0.012m 2 / g, 0.013m 2 / g, 0.022m 2 / g, 0.023m 2 / g or 0.034m 2 / g; (e) the average pore size of the nitrogen-doped hard carbon material is 1 to 3 nm, preferably 1.5 to 2 nm, such as 1.5 nm, 1.7 nm, 1.8 nm, 2.1 nm or 2.5 nm; (f) the volume of the micropores of the nitrogen-doped hard carbon material accounts for 35-70%, preferably 50-60%, such as 42.7%, 44.7%, 50.1%, 52.1%, 52.3% or 54.3% of the total pore volume of the nitrogen-doped hard carbon material; (g) The D50 particle size of the porous hard carbon particles is 5 to 10 μm, for example, 5 μm.
8. Use of the nitrogen-doped hard carbon material according to any one of claims 5 to 7 as a negative electrode material in a lithium ion battery.
9. A pole piece, characterized in that: It comprises the nitrogen-doped hard carbon material according to any one of claims 5 to 7.
10. An electrochemical device, characterized in that: It comprises the pole piece as claimed in claim 9.
Citation Information
Patent Citations
G-C3N4 / activated carbon compound photo-catalyst as well as preparation method and application of g-C3N4 / activated carbon compound photo-catalyst
CN104353482A
Preparation method of activated carbon carried carbon-doped graphite phase carbon nitride
CN106179444A
AC / g-C3N4 composite photocatalytic material and preparation method thereof
CN111085233A
Porous carbon / carbon nitride composite material and preparation method thereof
CN111725506A
Preparation method of coal tar pitch substrate layer porous carbon material
CN114751410A